Strategies for Enhancing Outdoor Learning Activities in Elementary Schools - Salsabila, Dania; Kholis, Nur; Kartikawati, Rr. Lisa; Maesaroh, Imas (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2024)
Outdoor learning, a pedagogical approach conducted outside traditional classroom settings, leverages natural environments to enhance educational experiences. This study examines the efforts of the Sidoarjo District Education and Culture Department in addressing challenges to implementing outdoor learning in primary schools and improving its overall quality. As a descriptive qualitative research method, data were collected through snowball sampling, in-depth interviews, documentation, and observations. Data were analyzed using Miles and Huberman's interactive model, encompassing data reduction, display, and conclusion drawing. The findings reveal that the department has adopted several strategies to optimize outdoor learning, including meticulous planning of logistics and activities, attentive oversight, enforcement of compliance through sanctions, provision of necessary facilities, and continuous monitoring of participating schools. These efforts aim to overcome logistical and interpretative challenges, ensuring outdoor learning is impactful and aligned with educational objectives. The study highlights the potential of outdoor learning to foster holistic student development and recommends further standardization, educator training, and collaboration with local communities to enhance its implementation.